Ecological stoichiometry and fungal community turnover reveal variation among mycorrhizal partners in their responses to warming and drought. Issue 1 (30th November 2021) - Zhang, Haiyang; Churchill, Amber C.; Anderson, Ian C.; Igwenagu, Chioma; Power, Sally A.; Plett, Jonathan M.; Macdonald, Catriona A.; Pendall, Elise; Carrillo, Yolima; Powell, Jeff R.
Abstract: Symbiotic fungi mediate important energy and nutrient transfers in terrestrial ecosystems. Environmental change can lead to shifts in communities of symbiotic fungi, but the consequences of these shifts for nutrient dynamics among symbiotic partners are poorly understood. Here, we assessed variation in carbon (C), nitrogen (N) and phosphorus (P) in tissues of arbuscular mycorrhizal (AM) fungi and a host plant ( Medicago sativa ) in response to experimental warming and drought. We linked compositional shifts in AM fungal communities in roots and soil to variation in hyphal chemistry by using high‐throughput DNA sequencing and joint species distribution modelling. Compared to plants, AM hyphae was 43% lower in (C) and 24% lower in (N) but more than nine times higher in (P), with significantly lower C:N, C:P and N:P ratios. Warming and drought resulted in increases in (P) and reduced C:P and N:P ratios in all tissues, indicating fungal P accumulation was exacerbated by climate‐associated stress. Warming and drought modified the composition of AM fungal communities, and many of the AM fungal genera that were linked to shifts in mycelial chemistry were also negatively impacted by climate variation. Our study offers a unified framework to link climate change, fungal community composition, and community‐level functional traits. Thus, our study provides insight into how environmental change can alter ecosystem functions via the promotion or reduction of fungal taxa with different stoichiometric characteristics and responses. Abstract : see also the Perspective by Pierre‐Luc Chagnon